2014
DOI: 10.1111/vcp.12145
|View full text |Cite
|
Sign up to set email alerts
|

Plasma biochemistry and urinalysis variables of koalas (Phascolarctos cinereus) with and without oxalate nephrosis

Abstract: Background Oxalate nephrosis is a highly prevalent disease in the Mount Lofty Ranges koala population in South Australia, but associated clinicopathologic findings remain undescribed. Objectives The aims of this study were to determine plasma biochemical and urinalysis variables, particularly for renal function and urinary crystal morphology and composition, in koalas with oxalate nephrosis. Methods Blood and urine samples from Mount Lofty Ranges koalas with oxalate nephrosis were compared with those unaffecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…That this prevalence is lower than has been found previously (55%) may be related to the larger cohort in the current study. Oxalate nephrosis has also been reported in other populations of koalas, but at only < 3% prevalence in New South Wales (n = 235) and up to 5% in Queensland (n = 20) . Oxalate nephrosis was found to be common in young koalas of TWC I, similar to an earlier study, and also in females, whereas previously no association with sex was identified.…”
Section: Discussionsupporting
confidence: 80%
“…That this prevalence is lower than has been found previously (55%) may be related to the larger cohort in the current study. Oxalate nephrosis has also been reported in other populations of koalas, but at only < 3% prevalence in New South Wales (n = 235) and up to 5% in Queensland (n = 20) . Oxalate nephrosis was found to be common in young koalas of TWC I, similar to an earlier study, and also in females, whereas previously no association with sex was identified.…”
Section: Discussionsupporting
confidence: 80%
“…Calcium oxalate crystals can exist in many forms, including envelope‐shaped dihydrate crystals (weddellite) and rod, “picket fence,” or dumbbell‐shaped monohydrate crystals (whewellite) . Unusual calcium oxalate crystals were recently reported in Koala urine and displayed a similar morphology to those reported here …”
Section: Discussionsupporting
confidence: 89%
“…1,27 A lower abundance of oxalate-degrading bacteria could increase the amount of oxalate absorbed from the gut into the bloodstream and increase the risk of renal oxalate deposition. in the Mount Lofty Ranges koalas compared with the two Queensland koalas in the previous study 23 could be partly related to the higher occurrence of oxalate nephrosis in Mount Lofty koalas.…”
Section: Discussionmentioning
confidence: 99%
“…in the Mount Lofty Ranges koalas compared with the two Queensland koalas in the previous study 23 could be partly related to the higher occurrence of oxalate nephrosis in Mount Lofty koalas. 1,27 A lower abundance of oxalate-degrading bacteria could increase the amount of oxalate absorbed from the gut into the bloodstream and increase the risk of renal oxalate deposition. This, coupled with the findings of a previous study in which dietary leaf oxalate content in Mount Lofty Ranges eucalyptus leaves was approximately double that of those in Moggill, Queensland, also supports this.…”
Section: Discussionmentioning
confidence: 99%